Pengaruh Ambient Interior Cafe Terhadap Pemilihan Tempat Bekerja Remote Worker di Era Pandemi COVID-19 - Sri Wahyuni Trisna, Ni Made; Utami, Ni Kadek Yuni; Effendi, Nabil Rahman (Waca Cipta Ruang, 2022)
The COVID-19 pandemic has boosted interest in working remotely, outside of an office, and the demand for these workers. During a pandemic, it is crucial to think about a cafe's comfort, especially the ambiance that is produced by the space's lighting, noise, and temperature. According to theory, the interior setting affects visitors' psychological well-being and can facilitate productive behavior. This study seeks to determine how the cafe's ambient environment—including lighting, sound, and temperature—affects remote workers' preferences for workspace. In order to determine the influence of the interior environment on deciding where to work during a pandemic, this study employed a quantitative methodology and surveyed 50 remote workers. Additionally, in-person observations at three well-known cafés in the Ubud area— Ruster Cafe, Milk and Madu, and Monsieur Spoon—were done to look at how the pandemic has affected the interior design. The study of the survey data demonstrated that the ambient interior's light, sound, and temperature, which can foster a sense of security and comfort against the transmission of the COVID-19 virus, had a substantial impact on remote employees' judgments about where to work during a pandemic. The findings of this study should assist café managers and owners in appreciating the importance of ambiance in their establishments. Keywords:Ambient Interior, Cafe, COVID-19 Pandemic, Remote Workers